Genetic Variability of Short Tandem Repeat Markers in Alcohol-Dependent Individuals in Baghdad - Qahtan Kadhim, Ali; Abd Ali Al-Khalidi, Rasha (Al-Nahrain Journal of Science, 2025)
Alcohol use disorder (AUD) arises from complex interactions among genetic, cultural, and environmental factors. Baghdad’s diverse population provides an ideal setting to explore these dynamics. We genotyped 23 autosomal short tandem repeat (STR) loci in 200 alcohol‑dependent individuals and 50 controls from Baghdad using the PowerPlex® 23 System between January 2023 and January 2025. Locus Penta E exhibited the highest gene diversity (GD = 0.962) and discrimination capacity (DC = 0.9310), whereas DYS391 and D10S1248 showed lower polymorphism (GD = 0.850). The combined random‑match probability across all loci was 9.66 × 10⁻²⁶. These results demonstrate that our 23‑locus STR panel delivers robust forensic resolution and establishes a reference dataset for future population‑genetic and AUD‑related research in Iraq.